Toxicity of Extracts and Fractions of Bangkal Leaves (Nauclea subdita (Korth.) Steud.) and Genjer (Limnocharis flava (L.) Buch) on the Bioindicator Artemia salina Leach - Arsyik Ibrahim; Sealti Puji Salea; Sri Windarti; M. Rahmad Ramadhan; Hidfdzur Rashif Rija'i; M. Arifuddin; Laode Rijai (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2026)
A study was conducted on the secondary metabolite content and toxicity testing of Artemia salina leach larvae using extracts from Bangkal leaves (Nauclea subdita (Korth.) Steud.) and Genjer plants (Limnocharis flava (L.) Buch). The objective of this study is twofold: firstly, to ascertain the compounds present in Bangkal leaf extract and Genjer plant extract, and secondly, to assess the toxicity levels of the extracts and fractions from Bangkal leaves and Genjer plants on Artemia salina Leach larvae. In this study, the extraction method employed was maceration with 96% ethanol as the solvent. The crude 96% ethanol extract was fractionated in stages using n-hexane, ethyl acetate, and n-butanol solvents based on polarity levels. The toxicity testing was conducted using the Brine Shrimp Lethality Test (BSLT) method, with Artemia salina Leach larvae serving as the bioindicator. A range of test concentrations were utilised, with each concentration having three replicates. The mortality of Artemia salina was observed after a 24-hour period and was analysed using the Reed and Muench method to determine the LC50 value. The results of the study demonstrated that the secondary metabolites present in the 96% ethanol extract of bangkal leaves com-prised the following groups of compounds: steroids, and triterpenoids, phenols, quinones, and saponins. The toxicity test results of the bangkal leaf extract and fractions yielded LC50 values of 418.79 ppm for the 96% ethanol extract; 716.14 ppm for the n-hexane fraction; 263.03 ppm for the ethyl acetate fraction; and 70,79 ppm for the extract n-buthanol fraction. Meanwhile, the toxicity test results of the genjer plant extract and fractions obtained an LC50 value of 490.23 ppm for the 96% ethanol extract; n-hexane fraction 551.31 ppm; ethyl acetate fraction 425.01 ppm; and n-butanol fraction extract 46.02 ppm. These results indicate that the n-butanol fraction of bangkal leaves and genjer plants have stronger cytotoxic activity than other fraction extracts.